TAX AWARENESS BY SUNAT AND ITS EFFECTS ON TAX COMPLIANCE. PERIOD 2021 - 2024 - Créspulo Ortega, Roosvelth (2024)
Objective: Analyze how the tax awareness promoted by the National Superintendence of Customs and Tax Administration (SUNAT) has influenced taxation processes in Peru in the periods 2021-2024. Method: Theoretical-explanatory, with a non-experimental design based on a quantitative analysis of the tax awareness activities implemented by SUNAT in Peru. The study focuses on the period 2021-2024 and uses statistical data and interviews with the objective of evaluating its impact on tax compliance awareness strategies. The sources include official reports from SUNAT, studies and reports from international organizations. The analysis is carried out using descriptive and inferential methods, to identify patterns and understand the perceptions and experiences of taxpayers and SUNAT officials. Results: The quantitative analysis shows an increasing trend in the tax compliance rate of the study period, with an increase from 78.2% in 2021 to 87.3% in 2024. Perception is the understanding of the importance of tax compliance, with a positive perception which went from 65.4% in 2021 to 80.6% in 2024. The awareness campaigns were effective, increasing participation in training programs and the dissemination of tax information. Conclusions: The study confirms that the tax awareness promoted by SUNAT has had a positive effect on tax compliance in Peru during the period 2021-2024. It is recommended to strengthen tax education, improve awareness campaigns and use information technologies to optimize the scope and effect of the initiatives. KEY WORDS: tax culture, tax compliance, tax awareness, SUNAT, Perú.